Residential tissues in Guayaquil: urban indicators relating to compactness and functionality - Pérez de Murzi, Teresa; Orejuela, Gaudy (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2023)
The Pascuales and Norte Zones represent the most recent advance of Guayaquil's urban footprint on the northern border of the homonymous canton. There coexist various residential forms that are making the city, at their own pace and with their own logics. This article aims to present a comparative analysis of residential fabrics based on the qualification of their morphology and the use of indicators related to compactness and functionality, one of the basic objectives of sustainable urbanism. The residential tissues were initially classified by their origin, type of promotion and permeability. The analysis, through a homogeneous comparison system and the use of quantitative parameters associated with compactness and functionality, makes it possible to visualize the neighborhood-scale behavior of this Ecuadorian city and establish a methodological scheme that can be integrated into diagnoses for planning purposes. The results point to important shortcomings in these fundamental contexts of local life, regardless of their origins and the actors involved in their production: deficit of public spaces, inadequate densities and insufficient mix of uses and urban functions.
Keywords: Urban morphology; residential areas; sustainable urbanism; Guayaquil